An example of Induction
Prove that (1+2+3+...+n) = n(n+1)/2
Step 1: Show true for n=1
(1) = 1 therefore true for n=1
Step 2: Assume true for some n=k
Since we assumed it is true for some n=k we know that
(1+2+3+...+k) = k(k+1)
-----
2
Step 3: Now show true for n=k+1
We know that the sum of (1+2+3+...+k+1) = (1+2+3+...+k+(k+1)) = (1+2+3+...+k)+(k+1)
now we can use our assumption from step 2: (1+2+3+...+k)=k(k+1)/2
let's substitute this into our equation and we get:
(1+2+3+...+(k+1))= (k(k+1)) + (k+1)
------
2
Now if we distribute the k we get (k^2+k) + (k+1)
-----
2
Now we simplify to get (k^2 +k+2k+2)
-----------
2
Which equals (k^2+3k+2) (k+1)(k+2) (k+1)((k+1)+1)
-------- = -------- = ----------
2 2 2
Therefore by induction:
(1+2+3...+n) = n(n+1)/2